Microplastics Contamination in a High Population Density Area of the Chao Phraya River, Bangkok - Anh Tuan Ta; Sandhya Babel; Andreas Haarstick (Institute for Research and Community Services, Institut Teknologi Bandung, 2020)
Microplastics (MPs) are distributed globally, including in aquatic environments. While a large number of studies on MPs in marine environments have been performed, few studies are available in freshwater environments. Therefore, the distribution of MPs in surface water and sediment from the Chao Phraya River at Tha Prachan, a high population density area of Bangkok, was investigated. Water samples were collected by a manta trawl with a net mesh size of 300 mm. Sediment samples were collected by a Van Veen grab sampler. The total number and concentration of MPs in the water samples were found to be 104 particles/m3 and 805.20 mg/m3, respectively. The dominant MPs were fragments, 0.5 to 1.0 mm in size, for the water samples. In the sediment, MPs were detected only in a size range of 0.053 to 0.5 mm with a total number and concentration of 2,290 particles/kg and 650 mg/kg, respectively. The presence of different types of MPs was confirmed by Fourier-transform infrared spectroscopy with a dominant abundance of polypropylene, polyethylene, and polystyrene. In brief, this study suggests that high levels of MPs occur not only in the water but also in the sediment of the Chao Phraya River at Tha Prachan area.